ANALISIS PENDAPATAN USAHA TANI PADI SAWAH DI DESA BUKIT PENINJAUAN II KECAMATAN SUKARAJA KABUPATEN SELUMA - Sarina; Wahyudi, Dwi; Fitria, Indah (University of Prof. Dr. Hazairin, SH, 2025)
This study aims to determine the differences in rice farming revenue between farmers who join farmer groups and those who do not join farmer groups in Bukit Peninjauan II Village, Sukaraja District, Seluma Regency. Samples were taken from 18 farmers who join farmer groups and 23 farmers who do not join farmer groups. The research was conducted using primary and secondary data. Data analyzed are production costs, revenues, income, R/C ratio. The results of the study show that the average land area for farmers who join farmer groups is 0.67 ha, and those who do not join farmer groups is 0.52 ha. The revenue of farmers who join farmer groups is Rp. 16,486,194/ha, average production costs of Rp. 9,188,049/ha, average income of Rp. 7,298,144/ha and R/C ratio of 1.79. Meanwhile, farmers who do not join farmer groups receive revenue of Rp.18,215,969/ha, average production cost Rp. 9,942,882/ha, average income Rp. 8,273,086/ha and R/C ratio of 1.85.